Therapeutical potential of mitochondrial reactive oxygen species in carcinogenesis - Palavan-Ünsal, Narçin; ARISAN, ELİF DAMLA (İstanbul Kültür Üniversitesi, 2009)
Mitochondria is a gatekeeper of cell death with dual function in survival and death decision. Mitochondria is also an important center for reactive oxgen species (ROS) production within most mammalian cells. The bulk of mitochondrial ROS generation can occur at relatively high rates compared to cytosolic ROS production and is primarily determined by metabolic conditions. This event contributes to mitochondrial damage in a range of pathologies and is also important in redox signalling from the organelle to the rest of the cell. Mitochondria targetting strategies in the therapeutical options are promising to increase the ROS generation to induce the apoptosis in cancer cells. Identification of molecular basis of therapeutic potential of mitochondrial ROS generation may provide more successful therapeutic tools in cancer therapy.
Keywords: Mitochondria; reactive oxygen; species; cell death; cancer